CLUSTER ANALYSIS OF RESEARCH AND DEVELOPMENT CAPACITY IN EUROPE - Brcanov, Dejan; Petrov, Viktorija; Bala, Karlo (The European Journal of Applied Economics, 2025)
The role of innovation in economic development cannot be overstated, particularly in the context of emerging market economies and newly industrialized countries, where it serves as a catalyst for national growth and international competitiveness Human capital plays an indispensable role in the development of knowledge economies, and its importance has become increasingly pronounced within the European Union as the region seeks to maintain its competitiveness in the context of green and digital transitions. Cluster analysis offers a methodologically robust approach to grouping countries based on similarities in their R&D profiles. By identifying clusters with comparable R&D characteristics, it is possible to gain nuanced insights into the strengths and weaknesses of national innovation systems. Understanding the distribution of R&D capacity across Europe can facilitate international collaborations and promote knowledge sharing among countries with similar strengths and challenges. This research paper aims to explore the clustering of European countries based on their R&D capacity, providing a comprehensive analysis of key metrics and their implications for national innovation strategies. The analysis was made regarding the most important aspects of distinction between four identified clusters that in total 35 European countries have been grouped to